Water and Sanitation for the 21st Century: Health and Microbiological Aspects of Excreta and Wastewater Management (Global Wate 2019
DOI: 10.14321/waterpathogens.7
|View full text |Cite
|
Sign up to set email alerts
|

General and host-associated bacteriophage indicators of faecal pollution

Abstract: The designations employed and the presentation of material throughout this publication do not imply the expression of any opinion whatsoever on the part of UNESCO concerning the legal status of any country, territory, city or area or of its authorities, or concerning the delimitation of its frontiers or boundaries. The ideas and opinions expressed in this publication are those of the authors; they are not necessarily those of UNESCO and do not commit the Organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 130 publications
(215 reference statements)
1
14
0
2
Order By: Relevance
“…Our findings are consistent with other studies where GB-124 phages were either not detected or detected at very low levels (close to the limit of detection) in non-human samples ( Payan et al, 2005 ; Ebdon et al, 2007 , 2012 ; Ogilvie et al, 2012 ; Harwood et al, 2013 ; McMinn et al, 2014 ; Diston and Wicki, 2015 ). These findings are also in line with the observations of Jebri et al (2017) , who suggest that source specificity is not absolute and, though seldom, Bacteroides host strains detect very low numbers of phages in the non-corresponding sources. Another possible reason for the presence of the GB-124 phages in a few porcine fecal samples could be the result of cross-contamination of porcine and human feces at the sample collection sites which were located in densely-populated household compounds.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with other studies where GB-124 phages were either not detected or detected at very low levels (close to the limit of detection) in non-human samples ( Payan et al, 2005 ; Ebdon et al, 2007 , 2012 ; Ogilvie et al, 2012 ; Harwood et al, 2013 ; McMinn et al, 2014 ; Diston and Wicki, 2015 ). These findings are also in line with the observations of Jebri et al (2017) , who suggest that source specificity is not absolute and, though seldom, Bacteroides host strains detect very low numbers of phages in the non-corresponding sources. Another possible reason for the presence of the GB-124 phages in a few porcine fecal samples could be the result of cross-contamination of porcine and human feces at the sample collection sites which were located in densely-populated household compounds.…”
Section: Discussionsupporting
confidence: 91%
“…Bacteriophages have been incorporated in recently developed guidelines for water quality monitoring ( NHMRC, 2011 ; European Commission, 2018 ; Health Canada, 2019 ). In particular, somatic bacteriophages and F-RNA phages have proved to be reliable indicators of fecal viral pollution and suitable for use in water treatment processes ( Jofre et al, 2016 ; Jebri et al, 2017 ). MST studies have used genogroups of F-specific RNA phages ( Jofre et al, 2011 ) and bacteriophages infecting selected strains of Bacteroides ( Tartera et al, 1989 ; Gómez-Dóñate et al, 2011 ; Jofre et al, 2014 ) to detect the source of fecal pollution in water environments.…”
Section: Introductionmentioning
confidence: 99%
“…The WMS and bioinformatic annotation strategy employed in this study identified fecal-associated microorganisms with finer taxonomic resolution; this has been observed in an earlier study ( Brumfield et al, 2020b ). Microbial species reported to be closely associated with the gut microbiota of specific animal groups ( Puig et al, 1999 ; Buchan et al, 2001 ; Newton et al, 2013 ; Shanks et al, 2013 ; Harwood et al, 2017 ; Jebri et al, 2017 ) suggest WMS can be used to shed light on potential sources of fecal pollution. Viruses were detected in samples collected after a rainfall, with crAssphage exhibiting a strikingly similar pattern to the HF183/BacR287 qPCR genetic marker, showing a change between dry weather and post rainfall samples.…”
Section: Discussionmentioning
confidence: 99%